What Explains EU Food Aid? An Econometric Analysis - Maas, Sarah; Justus Liebig University Giessen (My University, 2008)
This study investigates the determinants of EU food aid allocation among recipients for the period 1993-2003 from a political economy perspective. Thereby the analysis differentiates between emergency and non-emergency food aid which is, to the author’s best knowledge, not covered by preceding studies.
Keywords: ddc:330